2012
DOI: 10.4317/medoral.17518
|View full text |Cite
|
Sign up to set email alerts
|

Fracture resistance of roots filled with three different obturation techniques

Abstract: Objectives: The aim of this study was to compare in vitro root fracture resistance following root canal filling with AH 26 using lateral condensation, BeeFill, and Thermafil techniques. Study Design: Eighty extracted human mandibular premolars with similar dimensions were selected. In order to standardize the roots, measurements were taken in two separate regions of the teeth—at the cemento-enamel junction and 8 mm apically from the junction—buccolingual as well as mesiodistal for every tooth. Teeth were then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 27 publications
1
19
1
2
Order By: Relevance
“…In this study, it was found that the noninstrumented group had higher resistance than other prepared and filled groups. This finding is compatible with previous studies (9,27).…”
Section: Discussionsupporting
confidence: 94%
“…In this study, it was found that the noninstrumented group had higher resistance than other prepared and filled groups. This finding is compatible with previous studies (9,27).…”
Section: Discussionsupporting
confidence: 94%
“…In the work conducted by Teixeira (2004) statistically significant difference was not reported in the comparison of the fracture resistance between the teeth filled with cold lateral condensation or vertical condensation regardless of whether the root canal filling material was gutta‐percha or resilon (Teixeira et al, ). It was reported that there was not any significant difference in the comparison of fracture resistance between the cold lateral condensation, System B and Thermafill by using AH 26 and it was reported that these techniques did not increase the root fracture resistance of teeth significantly (Topcuoglu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that preparation weakens roots and makes teeth susceptible to vertical fracture is supported by previous studies. (21,22) In this study, canals prepared with step-back technique using standardized K-files created a taper of 0.02 in the apical third of the canal, whereas Helix rotary NiTi files created taper of 0.06, while the ProTaper variable taper within the same file. The ProTaper created a taper of 0.09 in apical third of the canal.…”
Section: Discussionmentioning
confidence: 89%